Infrared, Mid infrared and UV-Visible spectra study Cobalt chloride CoCl2. 6H2O molecule (Baghdad Science Journal, 2017)
IR, MIR, UV – Visible spectra have been studied for Cobalt chloride molecule (CoCl2. 6H2O) compound, In wide range spectra (40000 – 410) cm-1 specially MIR range. Assignment were achieved for the fundamental vibrational bands of (CoCl2 . 6H2O ) to symmetry stretching ?1 (?^+) Anti – symmetry stretching ?3(?^+), these bands are non-degenerate , and the bending band is ?2(?) is doubly degenerate thought they have activity in IR and Raman , which explain the weakness in symmetry of this molecule, the fundamental bands for the molecule are centered at the following wave numbers (615, 685, 795, 1115, 1340, 1375, 1616.35, 2091, 2386, 2410, 3364) cm-1 which are corresponding to wave lengths (16260, 14598, 12578, 8968, 7462, 7272, 6186, 4782, 4191, 4149, 2972 ) nmThe UV and visible spectra of the shows bands centered at (205.7) nm , (48614) cm-1 due to the electronic transition ( n ?^*) , other band centered at (512) nm, (19531) cm-1 due to (n ?^*) electronic transition .